Effects of Helicobacter pylori eradication on esophageal motility, esophageal acid exposure, and gastroesophageal reflux disease symptoms - Zhao, Tong; Liu, Fang; Li, Yongjun (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Effect of Helicobacter pylori (HP) eradication on gastroesophageal reflux disease (GERD) was not still entirely known. Few reports have investigated the mechanisms of relationships in H.pylori and GERD with prospective methods. The objective of this prospective clinical study was to explore the effects of HP eradication on GERD. Methods: Patients who diagnosed with both GERD and HP were included. The high-resolution esophageal manometry (HRM), 24-hour esophageal pH monitoring, and the Gastroesophageal Reflux Disease Questionnaire (GerdQ) were performed before and after successful eradication of HP, the data were compared using Statistical analysis. Results:Sixty-eight patients diagnosed with both GERD and HP were included. The After HP eradication group showed significantly decreased median distal contractile integral (DCI) [610.40(847.45) vs. 444.90(559.60)] and significantly increased median inefficient esphageal motility (IEM) [36.00(50.00) vs. 60.00(57.00)] in the HRM compared with the Before HP eradication group, indicating that HP eradication reduced esophageal peristalsis. The 24-hour esophageal pH monitoring showed that the longest reflux event, the percentage of time that the pH was <4, the number of reflux episodes, and the DeMeester score were were all statistically significant in the difference between the Before and After HP eradication group (P<0.05), suggesting that HP eradication increased esophageal acid exposure. The After HP eradication group also had a significantly higher GerdQ score than the Before HP eradication group (P<0.05). Conclusions: HP eradication reduced esophageal peristalsis, enhanced esophageal acid exposure, and aggravated GERD symptoms, suggesting that HP infection might be a protective factor for GERD.